2008
DOI: 10.2527/jas.2007-0692
|View full text |Cite
|
Sign up to set email alerts
|

Response to dietary phosphorus deficiency is affected by genetic background in growing pigs1

Abstract: Concern over the environmental effect of P excretion from pig production has led to reduced dietary P supplementation. To examine how genetics influence P utilization, 94 gilts sired by 2 genetic lines (PIC337 and PIC280) were housed individually and fed either a P-adequate diet (PA) or a 20% P-deficient diet (PD) for 14 wk. Initially and monthly, blood samples were collected and BW recorded after an overnight fast. Growth performance and plasma indicators of P status were determined monthly. At the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
22
1
1
Order By: Relevance
“…Few studies have been done to elucidate the effects of dietary P levels on gene expression (Hittmeier et al, 2006;Alexander et al, 2008). The results obtained in our study revealed that different aP levels in the diet altered the expression of the electron transport chain genes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Few studies have been done to elucidate the effects of dietary P levels on gene expression (Hittmeier et al, 2006;Alexander et al, 2008). The results obtained in our study revealed that different aP levels in the diet altered the expression of the electron transport chain genes.…”
Section: Discussionmentioning
confidence: 51%
“…However, little has been published on the analyses of gene expression when studying dietary levels of available phosphorus (aP) for pigs. Only two studies have shown that the need of aP is genotype specific (Hittmeier et al, 2006;Alexander et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…level of renal absorption of this nutrient. Confirming this proposition, Alexander et al (2008), when evaluating aP levels in diets for gilts from two genotypes from 8 to 80 kg, found that plasma levels of hormones associated with organic phosphorus homeostasis maintenance differed not only by phosphorus levels in their diets, but also between the genotypes evaluated. Levels of aP influenced (P<0.01) feed conversion (Table 2), which improved in a quadratic way up to a maximum response of 0.461% (Figure 3).…”
Section: Resultsmentioning
confidence: 64%
“…Frederick and Stahly (1998) studied dietary levels of aP for piglets from 7 to 23 kg and observed that the DFD decreased by increasing aP levels in their diets. Working with pigs during the growing and finishing phases, O'Quinn et al (1997) and Alexander et al (2008) reported that dietary aP deficiency resulted in higher fat thickness measured at the P2 position (10 th rib). The aP deficiencies in the referred studies corresponded to 75 and 80% of the aP levels suggested by the NRC (1998) for both growing and finishing phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation